PENDAMPINGAN PEMBUATAN KONTEN PROMOSI SEBAGAI MEDIA PEMASARAN BRANDING MARKETING UMKM DI WILAYAH KELURAHAN BABAT JERAWAT - Rabbani F, Ramzi Des; Supriyono, Supriyono (Batara Wisnu : Indonesian Journal of Community Services, 2025)
One of the main components of the growth of Micro, Small and Medium Enterprises (MSMEs) is marketing, especially in the current technological era. The purpose of this research is to learn about how promotional content creation functions as a tool for marketing brands and marketing of MSMEs in the Babat Jerawat sub-district area. With the increasing use of digital platforms and social media, MSMEs in Babat Jerawat have the opportunity to utilize content creation as a strategy to introduce their products, build brands and increase their competitiveness. In addition, this research found that MSMEs can help in product differentiation by creating consistent and relevant content. By presenting unique values ??from the products offered, MSMEs can more easily compete in the market with other business actors. On the other hand, the challenges faced by MSMEs in creating content are limited time and expertise in digital marketing. According to this research, creating promotional content has a positive effect on the branding of small and medium companies (MSMEs) in Babat Jerawat Village. Therefore, it is recommended that MSME players learn to create content and collaborate with influencers or digital marketing experts. With this, MSMEs in this area have the opportunity to exploit existing potential, increase sales, and strengthen their position in local and national markets.